Effect of vitamin-E on cypermethrin induced toxicity in cerebral cortex of wistar albino rats: A histological study - Mahat, Samyog; Jha, Chandra Bhusan; Shrestha, Shamsher; Koirala, Sarun (Journal of Karnali Academy of Health Sciences, 2020)
Backgrounds: Cypermethrin, class II pyrethroid pesticides, is commonly used in the agricultural field and house pest controls. Cypermethrin leads to neurotoxicity by crossing the blood-brain barrier, inducing oxygen stress in brain tissue. Vitamin-E is an antioxidant, involving in protecting membrane stability against free radicals induced peroxidants. This study was conducted to see the protective effect of vitamin-E on cypermethrin induced toxicity. Methodology: Fifty healthy Wistar albino rats of either sex weighing 150-200 grams were randomly selected & divided into five groups. Rats in first group served as control. Rats in second and fourth group were given cypermethrin orally at 20 mg/kg/BW for 14 and 28 days respectively. Rats in third and fifth group were give cypermethrin plus vitamin-E 2.5 ml/kg/BW orally for 14 and 28 days respectively. Rats were sacrificed and the brain was removed. Tissue processing was done. Histological analysis was carried out and statistical analysis was performed by the use of SPSS. Result: Cypermethrin treated rats showed decreased body and brain weight with severe neuronal vacuolation and decrease glial cell. While cypermethrin plus vitamin-E treated group showed increased body and brain weight, with normal glial cell and mild neuronal changes were observed. Conclusion: Cypermethrin in combination with vitamin-E minimized its harmful effect which was evidenced by improving body and brain weight gain and histological changes.